Synthesis of Hydrazones of Stobbe Acid and its Rearranged Products - Jacob, Jolly; Dave, M.A.; Parashar, S.N. (Asian Journal of Chemistry, 2016)
Stobbe anhydride (I and II) was condensed with diazonium salts of various atomatic amines to form hydrazones or dyes [I and II (a-c)] which were further treated with nucleophiles like 10% NaOH and NaBH4 to give various pyrazolinone [I and II (d-f)], [I and II (g-i)] and cyclic imide [I and II (j-l)] derivatives.